Transparent electro-optic ceramics: Processing, materials, and applications - Iva Milisavljevic; Man Zhang; Qinghui Jiang; Qing Liu; Yiquan Wu (Journal of Materiomics)
Transparent electro-optic (EO) oxide ceramics are known for their rapid EO effects. EO ceramics have several advantages over single-crystals, including variable size and shape, controllable chemical composition, superior mechanical properties, and low cost. Synthesis of high-performance transparent EO ceramics requires high purity of raw materials, high density, homogeneous composition, uniform grain size, and relatively wide bandgap. Powder synthesis and sintering are two of the critical steps involved in the fabrication of highly transparent EO ceramics. Using high-activity precursor powders has been effective in fabricating high-density ceramics that demonstrate excellent EO performance. The sintering process plays a crucial role in achieving this result, and currently, there are several sintering methods available for producing high-density ceramics, including hot-pressing, hot isostatic pressing, and spark plasma sintering. This review summarizes the recent progress in materials and processes used to develop transparent EO ceramics, including those based on lead zirconate titanate, lead magnesium niobate-lead titanate, and lead-free potassium sodium niobate. In addition, several novel applications of transparent EO ceramics, including light shutters, spectral filters, optical memory, as well as image storage and displays are reviewed. In the end, the review concludes with a discussion of future trends and perspectives.